Exploring the therapeutic landscape of Baccharoides anthelmintica: from traditional use to modern applications - Bhatt, Prachi Bhatt; Mahawar, Priya; Baunthiyal, Mamta (Ethnobotany Research and Applications, 2025)
Background: Baccharoides anthelmintica (also known as Vernonia anthelmintica), a medicinal plant from the Asteraceae family, is widely recognized in Ayurveda, Unani, Siddha, and traditional Chinese medicine. It has been traditionally utilized to address inflammatory issues, gastrointestinal disorders, skin ailments, and reproductive health problems. Its seeds are particularly esteemed for their capability to eliminate parasitic worms, which is reflected in its species name “anthelmintica.” Beyond its ethnomedicinal importance, the plant has piqued the interest of modern science for its potential pharmacological benefits and industrial applications. Methods: This review involved the examination of 25-30 original research studies, 10-15 review articles, classical literature, ethnobotanical surveys, and electronic databases (PubMed, Scopus, Web of Science, Google Scholar). Local traditional knowledge was also gathered from healers in Uttarakhand. Information on phytochemical components, pharmacological effects, and therapeutic uses was systematically compiled, with a focus on its anthelmintic properties. Results: Phytochemical investigations uncovered a variety of bioactive compounds, including sesquiterpene lactones, fatty acids, flavonoids and triterpenoids. These compounds exhibit antihelmintic, antimicrobial, antioxidant, anticancer, and anti-inflammatory effects. Their mechanisms include disruption of the parasite, inhibition of larval development, modulation of oxidative stress and induction of apoptosis in cancer cells. Conclusions: B. anthelmintica stands out as a valuable natural resource for the development of innovative anthelmintic and multi-target therapeutic agents. Its diverse phytochemical profile provides a scientific foundation for traditional claims; however, additional in vivo studies, clinical trials, and safety assessments are necessary for sustainable pharmacological and industrial use. Keywords: Baccharoides anthelmintica; Anthelmintic; Phytochemistry; Traditional Medicine; Asteraceae